The role of International Environmental Law in the application of Foreign Investment Law - Glave Mávila, Carlos (2016)
International Environmental Law (hereinafter, IEL) is entwined with other areas because environmental disputes are never raised in isolation of other legal fields. However, Foreign Investment Law (hereinafter, FIL) is recognized as one of the most reluctant areas when it comes to applying rules of IEL. As a consequence, it is important to remark the relevance of taking into account rules of IEL in investment disputes. In that sense, the aim of this paper is to highlight a progression in the relationship between FIL and IEL through the reasoning of decisions taken in investment arbitrations specifically dealing with expropriations. Consequently, some relevant investment arbitration awards that dealt with environmental concerns will be analyzed so as to recognize three stages of evolution. A complete lack of integration where the rules of IEL are not taken into account even though the parties have alleged them is the first period. Then, the application of concepts imported from human rights courts is the demonstration of a second phase. After that, a few more sophisticated approaches will be explained as examples of the connection between these fields of law and, finally, examples of cases where the protection of the environment is the key element of an investment dispute will be presented so as to remark that there is still a continuous evolution in progress.